Thermal and irradiation history of lunar meteorites by the 40Ar/39Ar technique: Dhofar 025, 309, 730, 733, 1442, Northwest Africa 6888, and Sayh al Uhaymir 449 - Trieloff, Mario; Korochantseva, E. V.; Buikin, A. I.; Hopp, Jens; Korochantsev, A. V. (Geochemistry, 2025)
We performed high-resolution 40Ar/39Ar dating of a suite of lunar meteorites from hot deserts: Dhofar 025, 309, 730, 733, 1442, Northwest Africa 6888, and Sayh al Uhaymir 449. The identification of terrestrial and lunar trapped argon components via isochrons allowed us to identify in situ radiogenic argon and to obtain proper chronological information. The last total reset ages of all studied samples are in the range of 3.1 to 4.2 Ga, coeval with the intense cratering period on the Moon and mare volcanism. Only Northwest Africa 6888 was totally reset <2.5 Ga ago. The most deeply buried breccia Dhofar 733 has the oldest age of 4.23 ± 0.04 Ga within this series of meteorites. Dhofar 733, 1442, and NWA 6888 were furthermore affected by recent impact events ≤1 Ga. All meteorites were irradiated by galactic cosmic rays on the surface of the Moon for several up to hundreds of Ma. A simple irradiation history is revealed for only one meteorite Dhofar 733 delivered to Earth within ~0.5 Ma. The comparison of exposure ages, solar argon abundances and partial loss of cosmogenic and radiogenic argon of lunar breccias indicates that long surface residence enhances accumulation of solar wind implanted 36Ar but also diffusive gas loss, most likely by surface thermal effects as solar and/or impact heating. The surficial regolith breccias Dhofar 025, 1442, NWA 6888, SaU 449 contain lunar trapped argon with 40Ar/36Ar ratios varying from 6 to 15, while the deep-derived breccia Dhofar 730 contains argon with (40Ar/36Ar)trapped ratio of 81. This could indicate that the composition of trapped argon in lunar meteorites may depend on rock layering depth. We suggest that the final capture of gases happens during sintering and agglutination along grain boundaries caused by thermal processes accompanying shock-induced compaction. Dhofar 1442 contains two distinct lunar trapped argon components with (40Ar/36Ar)trapped ratios of 14.58 ± 0.28 and 5.5 ± 0.7 indicating that lunar meteorites may contain more than one extraterrestrial trapped component incorporated during different thermal events. Our new 40Ar/39Ar ages of lunar meteorites significantly increase the number of high- resolution plateau age spectra, providing more compelling evidence of geochronologically meaningful pre 3.9 Ga ages. The different age distribution when compared to Apollo samples that were frequently dominated by Imbrium ejecta may be related to the fact that lunar meteorites provide a more random and thus complete sampling of the lunar surface, encompassing ejecta of older large basins, thereby favoring scenarios of more continuous or episodic pre 3.9 Ga bombardments. A possible scenario leading to episodic small body disturbances and bombardments involves close stellar encounters within the massive stellar cluster in which the sun resided during the first hundreds of million years of its lifetime.